Influence of blade rotation on the lightning stroke characteristic of a wind turbine. Issue 8 (8th April 2019) - Wang, Yu; Deng, Yeqiang; Liu, Yilu; Qu, Lu; Wen, Xishan; Lan, Lei; Wang, Jian
Abstract: The blades of a wind turbine rotate during normal operation. To investigate the influence of blade rotation on the lightning‐attracting ability of a wind turbine, a discharge test platform is designed for scaled wind turbines. The 50% impulse voltages and flash probabilities of the scaled wind turbines with gap distances of 1 to 8 m in the static and rotary conditions are determined by using the discharge test and selective discharge test. The discharge test for a single wind turbine with a gap of 1 to 2 m indicates that the breakdown voltages of the gap between the scaled turbine and electrodes increases with an increase in the blade rotation speed. However, the discharge test with a gap distance of 4 to 8 m indicates that the breakdown voltage of the fan decreases with an increase in the blade rotation speed. The test results of the scaled dual wind turbines experiment have the same rules. To explain this phenomenon, the influence of wind speed on the space‐charge distribution and electrical field intensity of corona discharge is simulated in the background of a target thundercloud. The rotation of the fan reduces the space‐charge density near the area of the blade tip, which leads to an increase in the field strength near the blade tip of the wind turbine and a decrease in the field strength away from the blade tip. This influence varies in short and long air gap, resulting in opposite relationships between discharge voltage and distance from the tip of the turbine. The results can provide a reference for the lightning protection of wind turbines.